Association between TAS2R38 gene polymorphisms and colorectal cancer risk: a case-control study in two independent populations of caucasian origin - Carrai, Maura; Steinke, Verena; Vodicka, Pavel; Pardini, Barbara; Rahner, Nils; Holinski-Feder, Elke; Morak, Monika; Schackert, Hans K.; Görgens, Heike; Stemmler, Susanne; Betz, Beate; Kloor, Matthias; et al. (PLOS ONE, 2011)
Molecular sensing in the lingual mucosa and in the gastro-intestinal tract play a role in the detection of ingested harmful drugs and toxins. Therefore, genetic polymorphisms affecting the capability of initiating these responses may be critical for the subsequent efficiency of avoiding and/or eliminating possible threats to the organism. By using a tagging approach in the region of Taste Receptor 2R38 (TAS2R38) gene, we investigated all the common genetic variation of this gene region in relation to colorectal cancer risk with a case-control study in a German population (709 controls and 602 cases) and in a Czech population (623 controls and 601 cases). We found that there were no significant associations between individual SNPs of the TAS2R38 gene and colorectal cancer in the Czech or in the German population, nor in the joint analysis. However, when we analyzed the diplotypes and the phenotypes we found that the non-taster group had an increased risk of colorectal cancer in comparison to the taster group. This association was borderline significant in the Czech population, (OR = 1.28, 95% CI 0.99-1.67; Pvalue = 0.058) and statistically significant in the German population (OR = 1.36, 95% CI 1.06-1.75; Pvalue = 0.016) and in the joint analysis (OR = 1.34, 95% CI 1.12-1.61; Pvalue = 0.001). In conclusion, we found a suggestive association between the human bitter tasting phenotype and the risk of CRC in two different populations of Caucasian origin.
Gesehen am 28.06.2022